2012
DOI: 10.4236/as.2012.35087
|View full text |Cite
|
Sign up to set email alerts
|

Diversity analysis of chickpea (<i>Cicer arietinum</i> L.) germplasm and its implications for conservation and crop breeding

Abstract: The exploration of genetically variable accessions is the key source of germplasm conservation and potential breeding material for the future. The more diverse group of cultivars provides an ample opportunity to breeders for releasing new and superior varieties, considering their quality traits for direct commercial utilization. In this study, we assessed the genetic diversity of Cicer arietinum 70 accessions from Pakistan and USA using morphological traits, seed protein and molecular markers. Based on four mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…In line with the present results, previous studies in chickpea, have reported positive and significant correlation of seed yield with the number of secondary branches plant -1 , number of pods plant -1 and biomass yield (Padmavathi et al, 2013), seed yield with biomass yield and harvest index (Ahmad et al, 2012). Other studies in chickpea, also reported negative and non-significant correlation of seed yield with plant height (Ali et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…In line with the present results, previous studies in chickpea, have reported positive and significant correlation of seed yield with the number of secondary branches plant -1 , number of pods plant -1 and biomass yield (Padmavathi et al, 2013), seed yield with biomass yield and harvest index (Ahmad et al, 2012). Other studies in chickpea, also reported negative and non-significant correlation of seed yield with plant height (Ali et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…The genetically discovery of variable accessions is the basic source to conservation of germplasm and potential breeding material for the future [18]. The further development of accession level data and subsequent comparison of this data across collections would greatly facilitate the identification of unique accessions [18].…”
Section: Discussionmentioning
confidence: 99%
“…The genetically discovery of variable accessions is the basic source to conservation of germplasm and potential breeding materials for the future [16]. The further development of accessions level data and subsequent comparison those of at the across collections would greatly facilitate identification of unique accessions [16]. Drought impacts affect most of plant life aspects such as decrease performance, growth, and resistance to other environmental stresses [17].…”
Section: Discussionmentioning
confidence: 99%